The role of guidance counsellors in the career development of adolescents and young adults with special needs (2011)
Guidance counsellors work individually and with other educators to meet the developmental needs of all students, including those with special needs or disabilities. Significantly, they focus on the academic, career, and personal/social developmental needs of all students, including those with special needs. Inconsistencies in the roles of practising guidance counsellors have caused some specialists in education to begin to address the emerging role of the counsellor regarding students with special needs, especially with respect to their career development. Since the level of happiness an individual exudes in life is closely related to the type of career the person chooses, and other career development activities relating to job retention and .advancement, guidance counsellors must endeavour to expose their students to several career development activities in order to help them to successfully, choose occupations, prepare for, enter into and progress in them. This paper discusses what career development is and some theories of career development. It also discusses factors that affect career choice. It highlights who the special needs persons are as well as the role of guidance counsellors in career development of special needs adolescents and young persons.